Linear function through two points

Algebra Level 2

What is f ( x ) f(x) , if it is a straight line going through ( 2 , 4 ) (2, 4) and ( 3 , 2 ) (3, -2) ?

6 x + 10 -6x+10 3 x + 10 -3x+10 6 x + 16 -6x+16 3 x + 7 -3x+7

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

A way to do this, which was not seen in high school, is to sum up a function g ( x ) g(x) going through ( 2 , 0 ) (2, 0) and ( 3 , 2 ) (3, -2) with another function h ( x ) h(x) going through ( 2 , 4 ) (2, 4) and ( 3 , 0 ) (3, 0) .

In other words:

f ( x ) = g ( x ) + h ( x ) f(x)=g(x)+h(x) f ( 2 ) = g ( 2 ) + h ( 2 ) = 0 + 4 f(2)=g(2)+h(2)=0+4 f ( 3 ) = g ( 3 ) + h ( 3 ) = 2 + 0 f(3)=g(3)+h(3)=-2+0

With a bit of math and logic, you can notice that if a function goes through points ( x 0 , 0 ) (x_0, 0) and ( x 1 , y 1 ) (x_1, y_1) , then it will be expressed as:

y = y 1 x 1 x 0 ( x x 0 ) y=\frac{y_1}{x_1-x_0}\cdot (x-x_0)

Knowing that m = y 1 x 1 x 0 m=\frac{y_1}{x_1-x_0} is the slope and that x 0 x_0 outputs as 0 0 .


Now that we identified the two functions, you get:

  • g ( x ) = 2 3 2 ( x 2 ) ) g(x)=\frac{-2}{3-2}\cdot (x-2))

  • h ( x ) = 4 2 3 ( x 3 ) ) h(x)=\frac{4}{2-3}\cdot (x-3))

f ( x ) = g ( x ) + h ( x ) f(x)=g(x)+h(x)

= ( 2 3 2 ( x 2 ) ) + ( 4 2 3 ( x 3 ) ) = ( \frac{-2}{3-2}\cdot (x-2)) + ( \frac{4}{2-3}\cdot (x-3))

= 2 ( x 2 ) 4 ( x 3 ) = -2(x-2)-4(x-3)

= 2 x + 4 4 x + 12 = -2x+4-4x+12

= 6 x + 16 = -6x+16

Your solution seems interesting, but I am not able to completely comprehend it, could you please provide a little bit of the way to get the boxed equation, I have just started learning coordinate geometry in school.

Vinayak Srivastava - 9 months, 1 week ago

Log in to reply

@Vinayak Srivastava, so what you're saying is that you have a hard time understanding how the curve y 1 x 1 x 0 ( x x 0 ) \frac{y_1}{x_1-x_0}\cdot (x-x_0) goes through ( x 0 , 0 ) (x_0, 0) and ( x 1 , y 1 ) (x_1, y_1) . Right?

Mateo Doucet De León - 9 months, 1 week ago

Log in to reply

Yes, I mean to say what is the derivation of that equation.

Vinayak Srivastava - 9 months, 1 week ago

@Vinayak Srivastava I added a visual proof and added more details. How is it?

Mateo Doucet De León - 9 months, 1 week ago
James Watson
Sep 4, 2020

We can determine the gradient of our line by using the formula m = y 2 y 1 x 2 x 1 \displaystyle m = \frac{y_2 - y_1}{x_2 - x_1} : m = 2 4 3 2 = 6 1 = 6 m = \cfrac{-2-4}{3-2} = \cfrac{-6}{1} = \boxed{-6} Now, our equation for our line looks like y = 6 x + c y=-6x+c but we need to find c c . For this, we can use one of our coordinates (I used the first one) to determine the value of our unknown constant: y = 6 x + c sub in x = 2 and y = 4 4 = 6 ( 2 ) + c 4 = 12 + c c = 4 + 12 = 16 \begin{aligned} y=-6x+c \xRightarrow{\text{sub in }x=2\text{ and }y=4} 4 &= -6(2) + c \\ \implies 4 &= -12 + c \\ \implies c &= 4 + 12 = \boxed{16} \end{aligned} Now we can form our equation and it is y = 6 x + 16 \green{\boxed{y=-6x + 16}}

Hi @James Watson , I saw that you made an explanation before I even did! I just wanted to point out that I created a completely different solution in case you'd like to see it.

Mateo Doucet De León - 9 months, 1 week ago

Log in to reply

i like your other solution quite a lot! more interesting than the traditional way!

James Watson - 9 months, 1 week ago

Than you! It' even possible to do this trick if you want to find a polynomial of any degree since you can decide at what x x value the output becomes 0 0 . Just use this: a ( x x 1 ) ( x x 2 ) ( x x 3 ) . . . a(x-x_1)(x-x_2)(x-x_3)...

Mateo Doucet De León - 9 months, 1 week ago

Same method, so I won't write a solution.

Typo : 6 6 \boxed{-6} \neq \red{\boxed{6}}

Vinayak Srivastava - 9 months, 1 week ago

Log in to reply

corrected - thanks!

James Watson - 9 months, 1 week ago

The equation for a straight line is given by f ( x ) = y = m x + c f(x) = y = mx + c , where m m is the gradient and c c is the y y -intercept of the straight line. Since the two points ( 2 , 4 ) (2,4) and ( 3 , 2 ) (3,-2) satisfy the equation, we have:

{ 4 = 2 m + c . . . ( 1 ) 2 = 3 m + c . . . ( 2 ) ( 2 ) ( 1 ) : 6 = m \begin{cases} \begin{aligned} 4 = 2m + c & ...(1) \\ -2 = 3m + c & ...(2) \end{aligned} \end{cases} \implies (2)-(1): \ -6 = m . Putting m = 6 m=-6 in ( 1 ) (1) , 4 = 12 + c c = 16 \implies 4 = -12 + c \implies c = 16 .

Therefore, f ( x ) = 6 x + 16 f(x) = \boxed{-6x+16} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...